CAUSAL MODEL OF SOME SOCIO-PSYCHOLOGICAL VARIABLES AS DETERMINANTS OF ACHIEVEMENT IN SECONDARY SCHOOL SOCIAL STUDIES (1995)
The study sought to obtain empirical evidence of the causal linkages between academic achievement and some socio-psychological variables, and to ascertain the extent to which these variables predict achievement in Social Studies. The study made use of ex-post facto design involving a sample of 624 Junior Secondary School class three students in thirty secondary schools in Oyo State. Each student responded to five different questionnaires and an achievement test in Social Studies. The data was analysed using stepwise multiple regression and path analysis statistics to answer the five research questions raised in this study. The research findings indicate that: 1. Only five of the variables viz: socio-economic status, gender, home language, attitude towards Social Studies and study habits influenced achievement in Social Studies. 2. Most of the variables that have indirect effects on students' achievement in Social Studies do so via study habits. 3. There is no direct effects of i. locus of control on achievement ii. gender on career aspiration iii. attitude towards Social Studies on career aspiration iv. locus of control on study habits v. test anxiety on achievement vi. career aspiration on achievement. 4. Total effects of the direct path accounted for 23.4% of the variation in students' achievement in Social Studies, while total effects of the indirect paths accounted for 9.0%. 5. The eight socio-psychological variables in the study when taken together were quite effective in predicting achievement in Social Studies with multiple R = 78; R(2) =61; Adjusted R(2) = .60; Standard Error = 6.57; R(2) Change = .61; F Change = 119.43. 6. Socio-economic status (VAR1) was the most effective variable in predicting achievement in secondary school Social Studies. 7. Locus of control, career aspiration, and test anxiety did not make any significant contribution to the prediction of achievement in Social Studies. The findings have important implications for the development of bumper and robust counselling package for secondary school students in line with the demand of the National Policy in Education.